1996
DOI: 10.1017/s0813483900004940
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Panic Attacks in Adolescents: Prevalence, Symptomatology, and Associated Features

Abstract: In this study, we examined the prevalence and nature of nonclinical panic attacks in 649 Australian youth and explored the relations between such attacks and measures of social support, stress, anxiety, depression, and fear. Full-blown attacks (attacks involving four or more symptoms with rapid onset) were reported by 104 of the youth (16%). Attacks were reported more frequently by girls than boys; however, age was unrelated to panic-attack status. Heightened levels of anxiety and fear, as well as stress in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
(49 reference statements)
2
13
1
Order By: Relevance
“…We found no gender differences in the symptoms of panic, but others have reported gender dif ferences with females experiencing more dizziness/faintness and nausea than males [King et al, 1997]. Like our study, King et al [1993] reported no age effects in the symptoms of PD, but interpretation of our findings needs to be taken with caution because we only included a small number of the PD patients younger than 13 years old (n ¼ 5).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…We found no gender differences in the symptoms of panic, but others have reported gender dif ferences with females experiencing more dizziness/faintness and nausea than males [King et al, 1997]. Like our study, King et al [1993] reported no age effects in the symptoms of PD, but interpretation of our findings needs to be taken with caution because we only included a small number of the PD patients younger than 13 years old (n ¼ 5).…”
Section: Discussioncontrasting
confidence: 52%
“…However, the prevalence of PD as well as panic attacks may vary according to the method of assessment (e.g., self questionnaires versus interviews, data obtained from youth versus that obtained from the family members), number of symptoms required for diagnosis, time period considered, and the population studied [Hayward et al, 1989]. For example, previous studies reported that the frequency of the symptoms of panic attacks in community samples of adolescents was between 43-60% [Hayward et al, 1989;King et al, 1993King et al, , 1997Macauly and Kleinknecht, 1989]. Nevertheless, the high frequency of panic attack symptoms could have been accounted for by the use of selfreports, which have been associated with high falsepositive rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terr (1979) reported that young victims of a kidnapping (ages 5-14 years) experienced panic attacks in response to external reminders of their experience. Other research has found that life stress, although not necessarily trauma, contributes to panic symptoms among children and adolescents (e.g., Bradley and Hood 1993;King et al 1996;Mattis and Ollendick 2002). In addition, a high prevalence of childhood trauma has been noted among adult females with panic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents with panic symptoms often experience significant functional impairments including school refusal (Hayward et al 1995;Masi et al 2000) and serious co-morbid conditions including separation anxiety, generalized anxiety, depression, dysthymia, specific phobia, attention-deficit hyperactivity disorder (ADHD), oppositional defiant disorder (ODD), and bipolar disorder (Doerfler et al 2007;King et al 1996;Masi et al 2000;Mattis and Ollendick 2002). Thus, it is important to better understand environmental and psychological factors that may contribute to the experience of panic symptoms among youth.…”
Section: Introductionmentioning
confidence: 99%